Midline 1 associated with Fas signaling enhances murine antigen-induced arthritis - Lukač, Nina; Flegar, Darja; Priselac, Sara; Kelava, Tomislav; Šućur, Alan; Filipović, Maša; Šisl, Dino; Fadljević, Martina; Radanović, Igor; Katavić, Vedran; Zimmermann, Nives; Grčević, Danka; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionRheumatoid arthritis is the most common immune-mediated joint disease, whose pathogenesis includes both innate and acquired immune mechanisms. Fas/Fas ligand system is considered to have a dual role in arthritis, inducing apoptotic cell death of hyperplastic synoviocytes and inflammatory cells, but also exerts proinflammatory effects. In our study, absence of Fas resulted in decreased accumulation of myeloid cells in affected joints.MethodsProportions of synovial hematopoietic cells were assessed by flow cytometry in wild-type and Fas −/− mice with antigen-induced arthritis. Effects of myeloid-specific ablation of Fas on the course of antigen-induced arthritis was assessed using Fasfl/LysMCre model. Arthritis was scored visually, histologically and by micro-computerized tomography. Transcriptome of sorted CD11b+Gr-1+ cells was analyzed by microarray, and effects of potential molecular driver Midline-1 (Mid-1) were analyzed in vitro and using Mid1 −/− mice.ResultsAmeliorated antigen-induced arthritis in Fas −/− mice is characterized by the lack of synovial accumulation of myeloid CD11b+Gr-1+ cells. However, myeloid-specific ablation of Fas was not sufficient to ameliorate arthritis, suggesting proinflammatory effects of Fas in multiple cell subsets in arthritis. Myeloid cells from Fas −/− mice downregulated limited number of genes including Mid1. Stimulation of bone marrow cells with low doses of soluble Fas agonist upregulated expression of Mid1. Inactivation of Mid1 had a variable anti-inflammatory effects in vitro and partial anti-arthritic effect in vivo.ConclusionFunctional Fas is required for the recruitment and accumulation of innate inflammatory cells in arthritic joints. This accumulation is not driven exclusively by mediators expressed in accumulated subset. Mid1 enhances inflammatory polarization of myeloid cells and promotes bone and cartilage degradation in arthritis.